TANGGUNG JAWAB PENGANGKUT TERHADAP KERUGIAN KONSUMEN ATAS TIKET YANG SUDAH DIBELI SEHUBUNGAN DENGAN TERJADINYA KEPAILITAN MASKAPAI PENERBANGAN - Dewi Ardiani, Desak Made; Tjukup, I Ketut (Kertha Desa; Vol. 01, No. 01, Maret 2013)
Bankruptcy can occur as a result of a corporation is deemed to be unable to pay anumber of debts of the company. An airline in bankruptcy will cause any harm to theconsumer over the tickets already purchased before the bankruptcy ruling wasannounced. Based on the foregoing it is necessary to know the carrier's responsibilitytowards the consumer losses over the tickets already purchased in connection with thebankruptcy of airlines. Writing method used is the juridical normative method. Bystudying the rules of Law relating to Legislation – liability of the carrier against a lossof consumers. Based on the Act_Law of the carrier's responsibility is to replace anylosses inflicted on passengers.
Keywords: Responsibility Of The Carrier, Consumers, Bankruptcy